2019
DOI: 10.1063/1.5109844
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chirality on fluorescence and resonance energy transfer

Abstract: Electronically excited molecules frequently exhibit two distinctive decay mechanisms that rapidly generate optical emission: one is direct fluorescence; the other, energy transfer to a neighboring component. In the latter, the process leading to the ensuing 'indirect' fluorescence is known as FRET: fluorescence resonance energy transfer. For chiral molecules, both fluorescence and FRET exhibit discriminatory behavior with respect to optical and material handedness. While chiral effects such as circular dichroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 81 publications
0
14
0
Order By: Relevance
“…Whilst the discussion thus far has focused on the coupling of electric dipole allowed transitions (μ-μ), the interplay between the μ-μ and μ-m coupling of a donor-acceptor system is also of relevance in energy transfer mechanisms involving chiral species. 56,89 For example, we recently demonstrated a 500-fold amplification of the |g lum | of a π-extended superhelicene, 21, when embedded in an achiral conjugated polymer matrix. 90 We proposed that the amplification arises through electrodynamic coupling between the electric and magnetic transition dipoles of the polymer donor and superhelicene acceptor, resulting in CP fluorescence resonance energy transfer (Figure 13).…”
Section: Intrinsic Chiroptical Activity: Chromophore Couplingmentioning
confidence: 99%
“…Whilst the discussion thus far has focused on the coupling of electric dipole allowed transitions (μ-μ), the interplay between the μ-μ and μ-m coupling of a donor-acceptor system is also of relevance in energy transfer mechanisms involving chiral species. 56,89 For example, we recently demonstrated a 500-fold amplification of the |g lum | of a π-extended superhelicene, 21, when embedded in an achiral conjugated polymer matrix. 90 We proposed that the amplification arises through electrodynamic coupling between the electric and magnetic transition dipoles of the polymer donor and superhelicene acceptor, resulting in CP fluorescence resonance energy transfer (Figure 13).…”
Section: Intrinsic Chiroptical Activity: Chromophore Couplingmentioning
confidence: 99%
“…Couplings involving at least one magnetic dipole e.g. (M1E1 3 )U typically have an enhanced CP emission compared to the pure electric dipole coupling, and do not have the same distance‐dependence as V, such that chiral energy transfer does not only occur between nearest neighbours [31, 32] . The FRET process has been previously shown to generate reasonably weak CPL (| g PL | ≈3×10 −3 ) from achiral small molecule acceptors when incorporated into chiral supramolecular structures such as nanohelices [33–36] …”
Section: Figurementioning
confidence: 99%
“…(M1E1 3 )U typically have an enhanced CP emission compared to the pure electric dipole coupling, and do not have the same distance-dependence as V, such that chiral energy transfer does not only occur between nearest neighbours. [31,32] The FRET process has been previously shown to generate reasonably weak CPL (j g PL j % 3 10 À3 ) from achiral small molecule acceptors when incorporated into chiral supramolecular structures such as nanohelices. [33][34][35][36] Here, we describe the highly dissymmetric photoluminescence (j g PL j > 0.1) of an enantiopure chiral p-conjugated small molecule acceptor (oxa [7]superhelicene, hereafter oxa- [7]H) embedded within a range of ACP donors (PFO, F8BT, F8PFB, Figure 1 and Supporting Information, SI).…”
mentioning
confidence: 99%
“…It is proposed that E1−M1 interactions and the interference between E1−E1 and M1−M1 couplings are dependent on the handedness of the energy donor and acceptor, which contribute greatly to chirality-sensitive FRET. 42 On the basis of that point, Fuchter and Andrews et al demonstrated the CPL amplification in another FRET process. The reported twisted polymer fibril here plays the role of chiral donor with high g lum , which can transmit energy to the oxa [7]superhelicene as an acceptor with poor intrinsic CPL performance.…”
mentioning
confidence: 94%
“…When it comes to the CPL in FRET, terms E1 and M1 are coined to describe this process, which arises from the electric (μ) and magnetic transition dipole moments ( m ), respectively. It is proposed that E1–M1 interactions and the interference between E1–E1 and M1–M1 couplings are dependent on the handedness of the energy donor and acceptor, which contribute greatly to chirality-sensitive FRET . On the basis of that point, Fuchter and Andrews et al demonstrated the CPL amplification in another FRET process.…”
mentioning
confidence: 99%